2002
DOI: 10.1128/iai.70.12.6541-6548.2002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Keratinocyte Growth Factor 1 Expression by Lipopolysaccharide Is Regulated by CD-14 and Toll-Like Receptors 2 and 4

Abstract: Periodontal disease is a chronic inflammatory condition that is associated with increased concentrations of gram-negative pathogenic bacteria and epithelial cell proliferation. Regulation of this proliferation is poorly understood but is most likely controlled by locally expressed growth factors. Keratinocyte growth factor 1, an epithelium-specific growth factor, is expressed by gingival fibroblasts, and its expression is regulated in a concentration-dependent manner by lipopolysaccharide. In this study, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 54 publications
2
31
0
1
Order By: Relevance
“…It had generally been thought that fibroblasts, epithelial cells, and endothelial cells do not express the membrane-anchored form (mCD14) and that complexes containing LPS and serum sCD14 interact with TLR4-MD-2 at the cell surface (4,20,26). However, recent reports suggest that mCD14 is indeed present in several fibroblast and endothelial cell lines (12,21,25).…”
mentioning
confidence: 91%
“…It had generally been thought that fibroblasts, epithelial cells, and endothelial cells do not express the membrane-anchored form (mCD14) and that complexes containing LPS and serum sCD14 interact with TLR4-MD-2 at the cell surface (4,20,26). However, recent reports suggest that mCD14 is indeed present in several fibroblast and endothelial cell lines (12,21,25).…”
mentioning
confidence: 91%
“…In fact, this LPS is a natural antagonist for the human endothelial E-selectin and IL-8 responses to E. coli LPS and other oral bacteria (11) and has recently been reported to be a TLR4 antagonist in some cell types (8,10,68). Furthermore, although several reports have demonstrated that this LPS utilizes TLR2 instead of TLR4 for host cell activation (5,26,37), it has also been reported to engage TLR4 (42,57) to facilitate gingival fibroblast activation through mCD14 (46,62).…”
mentioning
confidence: 99%
“…Chemokines attract lympho cytes and macrophages to the site of inflammation, which causes the formation of dental granulomas. Proinflammatory cytokines activate osteoclasts, which destroy interalveolar walls and cause the destruction of the teeth and jaws [18,19].…”
Section: Resultsmentioning
confidence: 99%